Students’ Critical Thinking Skills on Temperature and Heat Material through Educational Video Based on Local Wisdom - Maudy Nur Nur Achsani; Jasuri Jasuri; Susilawati Susilawati (Berkala Ilmiah Pendidikan Fisika, 2023)
This research aims to develop learning media products through educational videos based on local wisdom to improve critical thinking skills on temperature and heat. The research type is research and development using the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate). The study subjects were students of class X MIPA SMA Al-Hadi Girikusuma Mranggen Demak. Data collection techniques used are tests in the form of pretest-posttest, questionnaires, and documentation. The results showed that media and material expert validation obtained an average of 95.86% with a very feasible category. Student responses to learning media in the form of educational videos based on local wisdom obtained an average of 71.08% with a very interesting category. Improved critical thinking skills can be seen based on pretest and posttest scores. The results of the pretest and posttest calculations using the Gain Test obtained a result of 0.67 in the medium category. From the results of this study, it can be concluded that educational videos based on local wisdom can improve students' critical thinking skills in the heat and temperature materials developed that meet the criteria of being very suitable for students to use as learning media and can improve critical thinking skills. The implication is that this approach can be used as an effective alternative in teaching and learning that aims to develop students' critical thinking skills. Students can associate abstract concepts with their cultural and environmental contexts by incorporating local wisdom values in temperature and heat learning materials. This can increase their understanding and provide a more meaningful learning experience.